2018
DOI: 10.1016/j.yjmcc.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of cardiac L-type Ca2+ channels and their regulation in Drosophila: A novel genetically-pliable channelopathic model

Abstract: Dysregulation of L-type Ca channels (LTCCs) underlies numerous cardiac pathologies. Understanding their modulation with high fidelity relies on investigating LTCCs in their native environment with intact interacting proteins. Such studies benefit from genetic manipulation of endogenous channels in cardiomyocytes, which often proves cumbersome in mammalian models. Drosophila melanogaster, however, offers a potentially efficient alternative as it possesses a relatively simple heart, is genetically pliable, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 92 publications
1
19
0
Order By: Relevance
“…To link calcium transient to heart asynchrony, we first tested the propagation of calcium waves in normal and in asynchronously beating hearts. We applied the GCaMP3 fluorescent calcium sensor that allows detection of calcium waves in vivo (Limpitikul et al, 2018). As shown in Figure 4A, calcium waves perfectly shadow cardiac contractions in wild-type hearts, each calcium peak aligning with the beginning of contraction along the heart tube (here registered in segments A3 and A4).…”
Section: Resultsmentioning
confidence: 99%
“…To link calcium transient to heart asynchrony, we first tested the propagation of calcium waves in normal and in asynchronously beating hearts. We applied the GCaMP3 fluorescent calcium sensor that allows detection of calcium waves in vivo (Limpitikul et al, 2018). As shown in Figure 4A, calcium waves perfectly shadow cardiac contractions in wild-type hearts, each calcium peak aligning with the beginning of contraction along the heart tube (here registered in segments A3 and A4).…”
Section: Resultsmentioning
confidence: 99%
“…Old flies display altered intracellular cardiomyocyte calcium dynamics, with a prolonged transient decay, which promotes the extended periods of systole observed in senescent animals [23,44,59]. Recently, whole-cell patch clamp recordings of calcium currents across the membrane of isolated Drosophila cardiomyocytes confirmed the cells possess a conserved compendium of Land T-type calcium channels [60]. As in mammals, L-type (A1D in Drosophila) channels in flies serve as the main conduits for sarcolemmal calcium flux.…”
Section: Conserved Age-related Myocardial Changes In Drosophilamentioning
confidence: 99%
“…The root cause of these changes is not completely understood, but several lines of evidence indicate reduced myocardial β-adrenergic receptor density, their functional decline, and deficits in the β-adrenergic signaling cascade with advanced age [48,64,65]. Interestingly, Drosophila express components homologous to those of the vertebrate pathway, including adrenergic-like octopamine receptors (OctαRs, and OctβRs), adenylyl cyclase (rutabaga), phosphodiesterase (dunce), and both regulatory and catalytic subunits of protein kinase A (PKA), and their cardiac L-type calcium channels exhibit PKA-mediated current enhancement [60]. The expression of all aforementioned genes uniformly declines with age in Drosophila cardiomyocytes [15,24,66], suggesting old fly hearts may also exhibit blunted responses to adrenergic stimulation.…”
Section: Conserved Age-related Myocardial Changes In Drosophilamentioning
confidence: 99%
“…To make a link between calcium transient and heart asynchrony, we first tested propagation of calcium waves in normal and in asynchronously beating hearts. We applied the GCaMP3 fluorescent calcium sensor that allows detection of calcium waves in vivo (Limpitikul et al, 2018). As shown in Figure 4A, calcium waves underlie perfectly cardiac contractions in wild type hearts so that each calcium peak aligns with the beginning of contraction along the heart tube (here registered in segments A3 and A4).…”
Section: Tu-tagging-based Transcriptional Profiling Of Dm1 Models Witmentioning
confidence: 99%
“…Ca V 1.2 mutations are known to lead to diverse heartbeat dysfunctions (Splawski et al, 2004), and Ca V 1.2 deregulation is associated with DM1 (Rau et al, 2011). Importantly, the Drosophila counterpart of Cav1.2 (Ca-1αD) is also ensuring cardiac contractions and calcium transients in the fly heart (Limpitikul et al, 2018) suggesting a conserved role of Cav1.2/Ca-1αD in heart beating. Here, by following fluorescent calcium sensor (GCaMP3), we found that calcium waves underlie synchronous cardiac contractions and are disrupted in asynchronously beating DM1 fly hearts, implying that aberrant calcium transient in cardiomyocytes is associated with heart asynchrony.…”
Section: Calcium Regulators and Heart Functionmentioning
confidence: 99%